Extreme temperatures and sickness absence in the Mediterranean province of Barcelona: An occupational health issue - Utzet, Mireia; Ayala-Garcia, Amaya; Benavides, Fernando G.; Basagaña, Xavier (Frontiers in Public Health, 2023)
Objectives This study aims to assess the association between daily temperature and sickness absence episodes in the Mediterranean province of Barcelona between 2012 and 2015, according to sociodemographic and occupational characteristics. Methods Ecological study of a sample of salaried workers affiliated to the Spanish social security, resident in Barcelona province between 2012 and 2015. The association between daily mean temperature and risk of new sickness absence episodes was estimated with distributed lag non-linear models. The lag effect up to 1 week was considered. Analyses were repeated separately by sex, age groups, occupational category, economic sector and medical diagnosis groups of sickness absence. Results The study included 42,744 salaried workers and 97,166 episodes of sickness absence. The risk of sickness absence increased significantly between 2 and 6 days after the cold day. For hot days there was no association with risk of sickness absence. Women, young, non-manual and workers in the service sector had a higher risk of sickness absence on cold days. The effect of cold on sickness absence was significant for respiratory system diseases (RR: 2.16; 95%CI: 1.68–2.79) and infectious diseases (RR: 1.31; 95%CI: 1.04–1.66). Conclusion Low temperatures increase the risk of having a new episode of sickness absence, especially due to respiratory and infectious diseases. Vulnerable groups were identified. These results suggest the importance of working in indoor and possibly poorly ventilated spaces in the spread of diseases that eventually lead to an episode of sickness absence. It is necessary to develop specific prevention plans for cold situations.